2005
DOI: 10.1097/01.ijg.0000184832.08783.be
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caffeine on Intraocular Pressure

Abstract: In participants with open-angle glaucoma, this study identified a positive cross-sectional association between coffee consumption/higher caffeine intakes and elevated intraocular pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 17 publications
1
46
0
Order By: Relevance
“…Increased blood pressure after caffeine intake was reported in some studies, 4,7 which was not supported in some other studies. 8,28 Agaji et al 4 found an increase in systolic and diastolic blood pressure at 60 and 90 min after caffeine ingestion. Waring et al 31 evaluated the acute effects of caffeine on peripheral and central blood pressure in healthy individuals.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Increased blood pressure after caffeine intake was reported in some studies, 4,7 which was not supported in some other studies. 8,28 Agaji et al 4 found an increase in systolic and diastolic blood pressure at 60 and 90 min after caffeine ingestion. Waring et al 31 evaluated the acute effects of caffeine on peripheral and central blood pressure in healthy individuals.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported in some studies that caffeine increases intraocular pressure, 4,5,18 although no change in the intraocular pressure was found in the others. [28][29][30] Chandrasekaran et al 28 evaluated the effect of coffee intake on intraocular pressure. They found a significant positive association between coffee consumption and higher mean IOP levels in participants with open angle glaucoma after multivariate adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…In their investigation, Kang et al [39] found that for those with a self-reported family history of glaucoma, the risk of POAG with elevated IOP was associated with caffeine ingestion, while for those without family history, this relationship did not exist. In another cohort study [40], caffeine consumption was found to be associated with higher mean IOP in participants with open-angle glaucoma (OAG) than those without OAG. Possible explanations for the different responses to caffeine among different subjects may be that normal individuals with healthy drainage systems have much more ability to conduct aqueous than patients with glaucoma or OHT do.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, coffee consumption has been associated with elevated IOP in OAG patients in a cross-sectional study. 57 Kang et al 58 found that caffeine intake may be a risk factor for incident HTG for those with a family history of glaucoma. Our study did not find that the ingestion of one cup of caffeinated coffee adversely effected IOP, OPP, or OPA among participants with a family history of glaucoma.…”
Section: Eyementioning
confidence: 99%